Desain Pembelajaran Bilangan Bulat untuk Peserta Didik Tunarungu Berbasis Pendidikan Matematika Realistik Indonesia (PMRI) - Mariana Sanita Boru; Lukman El Hakim (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This article presents an analysis of the development of mathematics learning in deaf students (SMPLB-B). Deaf students are students with hearing loss partially (hard of hearing) or completely (deaf) so that it has an impact on the learning process. As educators, it is important to design the learning process to help students understand the material presented more easily by considering the characteristics and ability levels of deaf students. This article uses a development research method, namely the instructional development model (MPI). Learning development begins with carrying out an analysis of students, needs analysis and task analysis. Furthermore, it is described in detail about the objectives and learning outcomes to be achieved and adapted to the general learning objectives. The learning steps are presented in a coherent manner and also discussed formative and summative evaluation plans regarding the abilities of students and learning that is being developed. The results of the description of this article are in the form of a learning design on the topic of integers for deaf students using the Indonesian Realistic Mathematics Education (PMRI) approach which can be used as an option in the learning process.